New templates for HIV-1 antibody-based vaccine design. - Sattentau, Q; McMichael, A (2010)
A current strategy for the design of neutralizing antibody-based vaccines to prevent HIV-1 transmission is that of reverse engineering, starting from a neutralizing antibody and working back to reconstruct its epitope by structure-based design technology. However, the field has been impeded by a lack of appropriate antibodies for use as templates. Recently, new antibodies have been described that may fulfil this role, invigorating the field.